UV irradiation behavior of Salix psammophila sand barriers in the process of desertification control - Wang, Ruidong; Chen, Shichao; Gao, Yong (Frontiers in Plant Science, 2024)
Abstract：Salix psammophila sand barriers degrade under sunlight exposure, resulting in diminished protective performance and shortened service life in desertification control. To address the unresolved issue of photoinduced damage and degradation in sand barriers, we conducted simulations to assess the accelerated damage effect of ultraviolet rays during solar exposure of S.psammophila sand barriers. Our analysis focused on elucidating the mechanism of UV irradiation in sand barriers by examining the structural and material property changes that occur during the degradation process. The results indicated that: (1) The discoloration of sand barriers resulting from UV irradiation was primarily ascribed to the modification in lignin content; (2) The morphology and protective performance of S.psammophila sand barriers underwent significant changes following exposure to UV irradiation; The 96-day and 144-day time points of UV exposure are crucial for evaluating the extent of UV degradation in sand barriers. After 192 days of UV irradiation, there was a decrease in mass loss percentage by 3.62%, modulus of elasticity by 8.63%, and modulus of rupture by 6.74%. (3) The lignin, hemicellulose, and cellulose content decreased by 23.12%, 14.30%, and 6.96% respectively. The impact of UV irradiation on the polysaccharide (cellulose and hemicellulose) in S.psammophila sand barriers was relatively minimal. (4) The carbon binding form in S.psammophila sand barriers underwent a transformation, characterized by a significant decrease in C1 content and an increase in C2 and C3 content. This resulted in a gradual enhancement of the oxidation state and binding energy of carbon. Therefore, to prolong the utilization lifespan of S.psammophila sand barriers, it is essential to address the UV irradiation behavior from the perspective of inhibiting lignin reactions.